Perspektif dan Tantangan Perawat dalam Implementasi Family-Centered Care di NICU dan PICU: Suatu Narrative Review - Sri Hendrawati; Ristina Mirwanti; Siti Ulfah Rifa'atul Fitri (LPPM Institut Pendidikan Nusantara Global, 2026)
Family-Centered Care (FCC) is an essential approach in pediatric and neonatal healthcare that positions families as partners in care, particularly in high-complexity settings such as the Neonatal Intensive Care Unit (NICU) and Pediatric Intensive Care Unit (PICU). Although FCC has been widely recognized for its benefits to patients and families, its implementation in intensive nursing practice remains challenging. This narrative review aims to synthesize existing evidence regarding nurses’ perspectives and the challenges encountered in implementing FCC in NICU and PICU settings. A literature search was conducted across Cinahl from EbscoHost, Pubmed, ScienceDirect, and Google Scholar, covering publications from 2016 to 2025. Article selection was guided by the PEO framework, with nurses as the population, FCC implementation as the exposure, and perspectives and challenges in practice as the outcomes. Ten eligible articles were included and analyzed using a narrative synthesis approach. The findings indicate that nurses generally perceive FCC as a valuable and meaningful approach in neonatal and pediatric intensive care. However, implementation is constrained by multidimensional challenges, including high workload, limited time and resources, unclear boundaries of family involvement, complex communication with emotionally distressed families, and insufficient organizational and policy support. These challenges frequently place nurses in dilemmas between maintaining clinical safety and responding to family needs. Consistently across the reviewed studies, inadequate nurse-to-patient ratios and rigid institutional policies emerged as the primary barriers to effective FCC implementation. This review highlights the need for systemic support, structured education, and a shift toward a more collaborative and family-inclusive care culture. Strengthening institutional policies and enhancing nurses’ communication competencies are critical to promoting sustainable FCC implementation in NICU and PICU settings.